Implementasi pendidikan karakter Ki Hadjar Dewantara di Sekolah Dasar kelas awal pada era digital - Yuliwinarti, Evy Marita; Hendratno; Istiq’faroh, Nurul (Journal of Contemporary Issues in Primary Education, 2023)
Abstract: This research is motivated by the impact of the development of science and technology on the world of education which causes the personality of the younger generation to deteriorate. The aim of this research is to understand Ki Hadjar Dewantara's concept of character education and its implementation in elementary schools in the digital era. This research method is library research. This research method is carried out by reviewing literature sources, namely journals, books, scientific articles and other sources that support research. Character education is a systematic effort related to building culture by providing instruction in the growth and development of the child's soul and body in their nature so that the environment can help provide a positive influence on the child's physical and spiritual progress towards humane manners in the perfection of life. Elementary school is the second place for students in character education. The digital era is an age or era where everyone is technologically literate and everything is connected. Implementation of Ki Hadjar Dewantara's character education in elementary schools in the digital era, namely through Trikon Theory, Leadership Theory, and the Among System.